Response of chickpea (Cicer arietinum L.) to terminal drought: Leaf stomatal conductance, pod abscisic acid concentration, and seed set - Pang, J.; Turner, N.; Khan, T.; Du, Y.; Xiong, J.; Colmer, T.; Devilla, R.; Stefanova, Katia; Siddique, K. (Oxford University Press, 2017)
© 2016 The Author. Flower and pod production and seed set of chickpea (Cicer arietinum L.) are sensitive to drought stress. A 2-fold range in seed yield was found among a large number of chickpea genotypes grown at three dryland feld sites in south-Western Australia. Leaf water potential, photosynthetic characteristics, and reproductive development of two chickpea genotypes with contrasting yields in the feld were compared when subjected to terminal drought in 106kg containers of soil in a glasshouse. The terminal drought imposed from early podding reduced biomass, reproductive growth, harvest index, and seed yield of both genotypes. Terminal drought at least doubled the percentage of flower abortion, pod abscission, and number of empty pods. Pollen viability and germination decreased when the fraction of transpirable soil water (FTSW) decreased below 0.18 (82% of the plant-available soil water had been transpired); however, at least one pollen tube in each flower reached the ovary. The young pods which developed from flowers produced when the FTSW was 0.50 had viable embryos, but contained higher abscisic acid (ABA) concentrations than those of the well-watered plants; all pods ultimately aborted in the drough t treatment. Cessation of seed set at the same soil water content at which stomata began to close and ABA increased strongly suggested a role for ABA signalling in the failure to set seed either directly through abscission of developing pods or seeds or indirectly through the reduction of photosynthesis and assimilate supply to the seeds.